2020
DOI: 10.1101/2020.11.02.20224709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender-affirming care, mental health, and economic stability in the time of COVID-19: a global cross-sectional study of transgender and non-binary people

Abstract: Background Transgender and non-binary people are disproportionately burdened by barriers to quality healthcare, mental health challenges, and economic hardship. This study examined the impact of the novel coronavirus disease (COVID-19) pandemic and subsequent control measures on gender-affirming care, mental health, and economic stability among transgender and non-binary people globally. Methods We collected global cross-sectional data from 964 transgender and non-binary adult users of the Hornet and Her apps… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 49 publications
4
45
0
10
Order By: Relevance
“…These findings mirror the existing literature on mental health disparities of trans* and gender non-conforming people. For example, a recent study confirmed that due to the COVID-19 pandemic, access to gender-affirming resources and the ability of transgender and non-binary people to live according to their preferred gender has been reduced [ 56 ]. While gender-affirming care has repeatedly been found to improve physical and mental health of people with minoritized gender identities [ 57 , 58 ], access to it was already difficult for many individuals.…”
Section: Discussionmentioning
confidence: 99%
“…These findings mirror the existing literature on mental health disparities of trans* and gender non-conforming people. For example, a recent study confirmed that due to the COVID-19 pandemic, access to gender-affirming resources and the ability of transgender and non-binary people to live according to their preferred gender has been reduced [ 56 ]. While gender-affirming care has repeatedly been found to improve physical and mental health of people with minoritized gender identities [ 57 , 58 ], access to it was already difficult for many individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma, stress, and discrimination that contribute to health inequities among SGM likely impact vulnerability during the COVID-19 pandemic [ 7 , 8 ]. Structural factors such as high rates of unemployment and lack of health insurance among SGM that contributed to health inequity prior to COVID-19 are now worsening [ 12 , 13 , 44 ]. SGM are also more likely to experience homelessness that may increase exposure to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Studies across international settings have demonstrated that SGM communities have experienced increased depression and anxiety as a result of social distancing measures and worrying about health status related to COVID-19 [ 10 , 11 ]. Studies examining global sample of SGM using a smart-phone based “Gay Social Networking” app found that since the beginning of the COVID-19 pandemic SGM have been more likely to experience job loss, income reduction, and decreased access to gender affirming resources [ 12 , 13 ]. In the United States, Latinx SGM have experienced increased personal violence due to stay-at-home orders, and racial/ethnic minority status has been associated with increased risk of severe COVID-19 [ 9 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half screened positive for depression and 45% for anxiety. Suicidal ideation was also experienced by a significant number of study respondents [ 14 ].…”
Section: Introductionmentioning
confidence: 99%